Evaluasi Pelaksanaan Program Full Day School di Sekolah Menengah Kejuruan - Nila Oktaviana Kumang; Bambang Suteng Sulasmono (Universitas Negeri Malang, 2020)
Abstract: This study aims to evaluate the implementation of the full day school (FDS) program at Public Vocational High School 1 Pabelan. This type of research is evaluative research with descriptive qualitative methods using CIPP as an evaluation model. Data collection techniques using interviews, observation, and documentation. The results showed: (1) the context component was categorized as good because the FDS program was indeed needed by all stakeholders and parents, not just implementing policies from the government; (2) the input component is categorized as sufficient because it responds to the needs of all stakeholders and parents, adequate infrastructure and funds, the mechanism of implementing activities is clear, but the human resources of the number and competence of teachers are still lacking; and (3) the process component gets enough categories, because 80% of the programs are implemented according to plan, the resources are quite functional because the teacher facilitates the needs of students; although the funds provided are sufficient, but from the infrastructure, the number and competence of teachers is still lacking; and (4) the product component gets an adequate category because academic results do not show an increase, non-academic achievements have an increase but are not significant. Nevertheless, the objectives of implementing the FDS program were achieved because the students' character improved. Abstrak: Penelitian ini bertujuan untuk mengevaluasi pelaksanaan program full day school (FDS) di SMK Negeri 1 Pabelan. Jenis penelitian ini ialah penelitian evaluatif dengan metode kualitatif deskriptif menggunakan CIPP sebagai model evaluasi. Teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan: (1) komponen konteks mendapat kategori baik karena program FDS memang dibutuhkan oleh seluruh stakeholder dan orangtua, bukan hanya menerapkan kebijakan dari pemerintah; (2) komponen input mendapat kategori cukup karena menjawab kebutuhan seluruh stakeholder dan orangtua,sarana prasarana dan dana memadai, mekanisme pelaksanaan kegiatan jelas, tapi sumber daya manusia dari jumlah dan kompetensi guru masih kurang; dan (3) komponen proses mendapat kategori cukup, karena 80% program dilaksanakan sesuai rencana, sumber daya cukup fungsional karena guru memfasilitasi kebutuhan siswa; meskipun dana yang disediakan cukup, tetapi dari sarana prasarana, jumlah dan kompetensi guru masih kurang; dan (4) komponen produk mendapat kategori cukup karena hasil akademik tidak menunjukkan adanya peningkatan, prestasi non akademik ada peningkatan tetapi tidak signifikan. Meskipun demikian, tujuan dari pelaksanaan program FDS tercapai karena karakter siswa membaik.